Antimicrobial and Antioxidant Activities of Helichrysum Species from the Mediterranean Region of Turkey - ALBAYRAK, SEVIL; SAGDIC, OSMAN; AKSOY, AHMET; HAMZAOGLU, ERGIN (Asian Journal of Chemistry, 2010)
In this study, it was investigated the antioxidant, antiradical and antimicrobial activities of methanolic extracts from three Helichrysum species [H. pamphylicum Davis & Kupicha, H. sanguineum (L.) Kostel, H. chasmolycicum P.H. Davis (Asteraceae)]. The total phenolic contents of methanolic extracts ranged from 71.51 to 119.85 mg gallic acid/g dry extract. H. pamphylicum methanolic extract showed the highest antioxidant activity (173.58 mg ascorbic acid/g dry extract). Antiradical activity of H. sanguineum methanolic extract was the highest (IC50 =12.90 μg/mL) in DPPH assay. All the extracts were investigated for antimicrobial effect against 15 species of microorganisms containing thirteen bacteria and two yeasts. The methanolic extracts were inactive against Escherichia coli and Proteus mirabilis. The most sensitive bacteria were Klebsiella pneumoniae for H. pamphylicum, Staphylococcus aureus (B), Proteus vulgaris for H. sanguineum and S. aureus (B) for H. chasmolycicum. All of the Helichrysum extracts showed similar antimicrobial activities against microorganisms tested. In conclusion, this study provides the basis for the present rapidly increasing interest for the use of natural antioxidants and antimicrobials as functional food ingredients and/or as food supplements.